The Effects of Minimum Wage on the Employment of Temporary Employees - 김상일; 구정호; 김세희 (관리회계연구, 2024)
[Purpose]The purpose of this study is to examine the effect of an increase in the hourly minimum wage on the employment of temporary employees and their operating performance when sales decrease. [Methodology]For 13,818 firm－year samples of 2010－2020 years, we use OECD data to obtain the real minimum wage in Korea and we download the financial data from DataGuide. And we adopt the cost stickiness models of Anderson et al. (2003). [Findings]The results show that an increased hourly minimum wage allows for greater asymmetry in the employment of temporary employees. Subsample tests show that the dismissal of temporary employees is more pronounced for the subgroup with labor unions or in non－high－tech industries. [Implications]This study suggests that minimum wage increases may unintentionally lead to a reduction in temporary employee employment, the group the policy seeks to benefit. Therefore, policy－makers need to carefully design minimum wage policies to avoid unintended consequences such as the dismissal of temporary employees.
Keywords: Minimum Wage; Temporary Employee; Cost Stickiness; Regular Employee; Operating Performance; 최저임금; 비정규직; 원가 하방경직성; 정규직; 영업성과